Platystele peruviana sp nov. (Orchidaceae), the smallest orchid from Peru - Rizo Patrón, Federico L. (Phytotaxa, 2022)
A new orchid species is described, Platystele peruviana, from Oxapampa, Pasco, Peru, and can be considered, at this moment, the smallest orchid in the country. This species differs from other related species by the morphology of the ovate lip with circular glenion and the lateral sepals parallel, subfalcate and connate. A brief history of Platystele is provided along with the botanical description and illustrations of the new species. Finally, a key to the Peruvian Platystele species is provided, in English and Spanish.